PEMANFAATAN QRIS PADA PEDAGANG PENERIMA PKH - Ade Sakinah Rahma; Nazwa Wa’Hidaini; M.Vebrek Wabarokatuh; Muhammad Gandung (Abdi Jurnal Publikasi, 2026)
The development of digital payment technology has driven changes in transaction patterns in society, including in the micro-business sector. One of the widely used non-cash payment innovations is Quick Response Code Indonesian Standard (QRIS). However, the utilization of QRIS among small traders, especially those receiving the Family Hope Program (PKH), is still low due to limited digital literacy and information access. This Community Service Program (PKM) aims to examine and increase the utilization of QRIS among PKH traders as an effort to support financial inclusion and transaction efficiency. The methods used include field observations, interviews, as well as socialization and mentoring on QRIS usage to target traders. The expected results of this activity are increased understanding and skills of PKH traders in using QRIS as a payment tool, increased transaction convenience for consumers, and the creation of more orderly and transparent financial records. Through this program, it is hoped that PKH traders can adapt to digital technology developments to improve business competitiveness and support community economic welfare.